Structure and expression of dna methyltransferase genes from apomictic and sexual Boechera species. (April 2017) - Taşkin, Kemal Melik; Özbilen, Aslıhan; Sezer, Fatih; Hürkan, Kaan; Güneş, Şebnem
Graphical abstract: Highlights: The structure of the DNMTs genes in apomict and sexual Boechera species are highly similar to A. thaliana orthologs. While the expression levels of MET1 and CMT3 do not differ much, DRM2 upregulated in developing seeds of apomictic Boechera spp. Our results suggest that a deregulation in the DNA methylation machinery during endosperm development may require for apomixis. Abstract: In this study, we determined the structure of DNA methyltransferase (DNMT) genes in apomict and sexual Boechera species and investigated the expression levels during seed development. Protein and DNA sequences of diploid sexual Boechera stricta DNMT genes obtained from Phytozome 10.3 were used to identify the homologues in apomicts, Boechera holboellii and Boechera divaricarpa . Geneious R8 software was used to map the short-paired reads library of B. holboellii whole genome or B. divaricarpa transcriptome reads to the reference gene sequences. We determined three DNMT genes; for Boechera spp. METHYLTRANSFERASE1 ( MET1 ), CHROMOMETHYLASE 3 ( CMT3 ) and DOMAINS REARRANGED METHYLTRANSFERASE 1/2 ( DRM2 ). We examined the structure of these genes with bioinformatic tools and compared with other DNMT genes in plants. We also examined the levels of expression in silique tissues after fertilization by semi-quantitative PCR. The structure of DNMT proteins in apomict and sexual Boechera species share common features. However, the expression levels of DNMT genes were different in apomict and sexual Boechera species. We found that DRM2 was upregulated in apomictic Boechera species after fertilization. Phylogenetic trees showed that three genes are conserved among green algae, monocotyledons and dicotyledons. Our results indicated a deregulation of DNA methylation machinery during seed development in apomicts.